2019
DOI: 10.1093/pm/pnz101
|View full text |Cite
|
Sign up to set email alerts
|

Relief of Neuropathic Pain Through Epidermal Growth Factor Receptor Inhibition: A Randomized Proof-of-Concept Trial

Abstract: Objective Case reports and a case series have described relief of neuropathic pain (NP) after treatment with epidermal growth factor receptor inhibitors (EGFR-Is). These observations are supported by preclinical findings. The aim of this trial was to explore a potential clinical signal supporting the therapeutic efficacy of EGFR-Is in NP. Methods In a proof-of-concept trial using a randomized, double-blind, placebo-controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 41 publications
(51 reference statements)
2
29
1
Order By: Relevance
“…An intriguing theme emerging from these distinct interactomes is the prominence of epidermal growth factor receptor (EGFR) ligands as possible mediators of interactions between diseased tissue and mouse and human nociceptors. This finding is consistent with recent preclinical and clinical findings suggesting efficacy of blocking EGFR signaling for chronic pain (Kersten et al, 2013;Kersten et al, 2015;Martin et al, 2017;Kersten et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…An intriguing theme emerging from these distinct interactomes is the prominence of epidermal growth factor receptor (EGFR) ligands as possible mediators of interactions between diseased tissue and mouse and human nociceptors. This finding is consistent with recent preclinical and clinical findings suggesting efficacy of blocking EGFR signaling for chronic pain (Kersten et al, 2013;Kersten et al, 2015;Martin et al, 2017;Kersten et al, 2019).…”
Section: Introductionsupporting
confidence: 92%
“…Animal pain models suggest that EGFR activation by epiregulin encoded by the EREG gene promotes inflammatory and neuropathic pain and that EGFR signaling is critical for pain promoting effects of opioids (Martin et al, 2017;Puig et al, 2020). Finally, several clinical trials have been done with EGFR inhibitors for neuropathic pain and some of these have been positive (Kersten et al, 2013;Kersten et al, 2015;Kersten et al, 2019). Our results point to a diversity of EGFR ligands that are upregulated in painful tissues such as joints of people with rheumatoid arthritis and in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Based on this, we performed a randomised, placebo-controlled double-blind proof-of-concept trial of cetuximab in patients with severe, treatment-refractory NP due to non-malignant compressed peripheral nerves (n=7) or complex regional pain syndrome (n=7). 22 This so-called NoTOPain trial (NoTOPain: Novel Treatment Option for neuropathic Pain) reported relatively high response rates among treatment-resistant patients and the magnitude of pain relief seen in those patients who benefited was encouraging. 22 Eight of the trial patients chose to continue with oral EGFR-Is after study completion.…”
Section: Case Reportmentioning
confidence: 99%
“…22 This so-called NoTOPain trial (NoTOPain: Novel Treatment Option for neuropathic Pain) reported relatively high response rates among treatment-resistant patients and the magnitude of pain relief seen in those patients who benefited was encouraging. 22 Eight of the trial patients chose to continue with oral EGFR-Is after study completion. The current case report describes the clinical course of one of the trial participants during and for 48 months after the NoTOPain trial.…”
Section: Case Reportmentioning
confidence: 99%